2016
DOI: 10.1186/s13567-016-0400-7
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the virulence of a recombinant influenza virus expressing the naturally truncated NS gene from an H3N8 equine influenza virus in mice

Abstract: Equine influenza virus (EIV) causes a highly contagious disease in horses and other equids. Recently, we isolated an H3N8 EIV (A/equine/Kyonggi/SA1/2011) from a domestic horse in South Korea that exhibited symptoms of respiratory disease, and found that the EIV strain contained a naturally mutated NS gene segment encoding a truncated NS1 protein. In order to determine whether there was an association between the NS gene truncation and viral virulence, a reverse genetics system was applied to generate various N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…IFNs are a group of signaling proteins that are produced by cells in response to viral infections, and they play a key role in activating the host immune system to fight off the virus [28]. Truncation of the effector domain of the NS gene can affect viral replication by altering the ability of the virus to evade the host immune response [15,16,29]. The effector domain of NS1 includes the PKR binding site, p85β-binding site, CPSF30-binding site, and PDZ domain, which act to evade the host antiviral In the 2nd week after the 2nd vaccination, mice were euthanized to obtain the spleen (n = 5) and lungs (n = 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IFNs are a group of signaling proteins that are produced by cells in response to viral infections, and they play a key role in activating the host immune system to fight off the virus [28]. Truncation of the effector domain of the NS gene can affect viral replication by altering the ability of the virus to evade the host immune response [15,16,29]. The effector domain of NS1 includes the PKR binding site, p85β-binding site, CPSF30-binding site, and PDZ domain, which act to evade the host antiviral In the 2nd week after the 2nd vaccination, mice were euthanized to obtain the spleen (n = 5) and lungs (n = 5).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the SA1 strain, which has a naturally truncated NS gene, it was revealed that the virus showed significantly increased expression of antiviral and pro-inflammatory genes in vitro [16]. Furthermore, in a mouse model, the recombinant PR/8 virus containing the concerned truncated NS gene showed dramatically reduced virulence, and the level of IFN-g cytokines was statistically elevated [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mRNA levels of IFN-β, IL-1β, and TNF-α in mouse lungs of the WSN-NS1-K108R-infected group were significantly higher than those in the other two groups at 3 dpi, which indicated that NS1-108R was less efficient at inhibiting the production of innate antiviral cytokines at 3 dpi in mice. The NS1 protein of influenza virus is a virulence factor that inhibits the antiviral immunity of the infected host, and C-terminal truncation has been widely used as a strategy to generate attenuated virus vaccine candidates [39]. One mechanism used by NS1 to inhibit the IFN response is through direct binding and sequestration of RNA as well as direct interaction with TRIM25 and complex formation with the RNA sensor RIG-I, resulting in inhibition of the activation of the RIG-I CARD and hence inhibition of IRF3 activation [12].…”
Section: Discussionmentioning
confidence: 99%